"And the word became . . . gossip?" Unhinging the Samaritan woman in the age of #MeToo. (May 2020) - Parker, Angela N.
This article examines the Samaritan woman's speech in John 4. More specifically, this article employs a womanist hermeneutic of "unhinging" to argue that the Samaritan woman serves as an example for women who struggle with issues of testimonial authority in the midst of silence and shame at the hand of their communities. Thinking through the dynamic of the #MeToo movement and issues of power, testimonial authority, and trauma, this article interrogates the phrases dia ton logon ("because of the word") and dia tēn sēn lalian ("because of your gossip") to argue that, although the Samaritan woman possesses agency and voice with the power to engage Jesus in theological discussions, interpreters of her story still interrogate her for perceived sexual indiscretions to the point of her continued silence and shame in the history of interpretation. This article wrestles with both the Johannine author's and the Samaritan community's reducing her agency and voice to the point that readers live in ambiguity regarding her status. Concluding thoughts imagine what "living in ambiguity" looks like as a way to unhinge not only the Samaritan woman but contemporary African American church women from the experiences of silence and shaming in the age of #MeToo.